Association Between Triglyceride Glucose Index and Risk of Carotid Plaques in Asia: A Systematic Review and Meta-Analysis - Zhuang, Jiaxin; Qiu, Suyi; Fang, Tingfeng; Ding, Meihao; Chen, Miaoqi (Hormone and Metabolic Research, 2025)
The triglyceride glucose (TyG) index is used to assess insulin resistance, which is associated with the occurrence and development of cardiovascular diseases, but the risk of carotid plaques is controversial in Asia. We searched PubMed, Embase, Scopus, and Cochrane Library for articles published up to October 15, 2023, to assess the association and dose-response association of the TyG index with the risk of carotid plaques in Asia. The random effects model was used to calculate the effect estimates and 95% confidence intervals (CIs). A total of 534 articles were retrieved, and eleven studies were selected, involving 145 218 Asian participants. When the TyG index was analyzed as a categorical variable, compared with the low TyG index, the high TyG index increased the risk of carotid plaques (OR=1.38, 95% CI: 1.20, 1.60, p<0.001). As continuous variables were analyzed, similar results were observed (OR=1.33, 95% CI: 1.22, 1.45, p<0.001). Meanwhile, dose-response analysis showed that the risk of carotid plaque increased by 1.03 times for every unit increase in the TyG index (RR=1.03, 95% CI: 1.02, 1.03, p<0.001). Our meta-analysis indicates an association between the TyG index and the risk of carotid plaques in Asia. Further studies are required to substantiate these findings.
Keywords: triglyceride glucose index; carotid plaques; Asian; meta-analysis; dose-response analysis